2003
DOI: 10.1103/physrevb.68.233301
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic phonon sidebands in the emission line of single InAs/GaAs quantum dots

Abstract: We present an experimental and theoretical study of the existence of acoustic phonon sidebands in the emission line of single self-assembled InAs/GaAs quantum dots. Temperature-dependent photoluminescence measurements reveal a deviation from a Lorentzian profile with the appearance of lateral sidebands. We obtain an excellent agreement with calculations done in the framework of the Huang-Rhys formalism. We conclude that the only relevant parameter for the observation of acoustic phonon sidebands is the linewid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
117
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 15 publications
10
117
3
Order By: Relevance
“…A broad shoulder to the quantum dot line shape due to phonons has also been observed in CW-photoluminescence measurements. 25,26 In the case of the ideal two-level atom, the 3p -peak has a slight arrow-head like shape. The exciton-phonon interaction appears to accentuate the arrow-head.…”
Section: Influence Of Detuningmentioning
confidence: 99%
“…A broad shoulder to the quantum dot line shape due to phonons has also been observed in CW-photoluminescence measurements. 25,26 In the case of the ideal two-level atom, the 3p -peak has a slight arrow-head like shape. The exciton-phonon interaction appears to accentuate the arrow-head.…”
Section: Influence Of Detuningmentioning
confidence: 99%
“…2͑b͒ ͑=1.9 meV͒, ␥͑⌫ LO ͒ is smaller ͑larger͒ than that of the two-dimensional exciton case by two to three times ͑three to four times͒, 37 while very similar to the zero-dimensional case. 38 The deviation of the fitting curve above 80 K for 0-0 LL and above 90 K for 1-1 LL is possibly associated with carrier delocalization and/or deionized impurities at high temperatures. 39 ⌫ 0 ͑ϳ1.9 meV͒ indicates that the SF pulse duration is shorter than 700 fs ͑ =2ប / ⌫ 0 ͒ while the temperature dependence of B TH ͑T͒ agrees with the dephasing dynamics in a zero-dimensional system.…”
Section: Temperature Dependencementioning
confidence: 99%
“…Temperature-dependent measurements have shown that the line-shape can be described by the superposition of the so-called zero-phonon line (ZPL) and broad side-bands extending on several meV [7][8][9]. These side-bands arise from the radiative recombination of electron-hole pairs assisted by the emission and the absorption of acoustic phonons.…”
mentioning
confidence: 99%